Let x be the number of $1 bags that we bought.
An, let y be the number of $2 bags that we bought.
So the total cost equation is:
We may re-write this as:
`x + 2y = 600`
Since the number of $1 bags (x) is twice the number of $2 bags (y), then:
`x = 2y`
Substitute this to the total cost equation.
Divide both sides by 4, to isolate the y.
So, we bought 150 pieces of $2 bag.
Then, substitute this to x = 2y.
And, we ordered 300 pieces of $1 bag.
Then, add the values of x and y to get the total number of bags.
`x + y = 300+150 = 450`
Hence, we bought a total of 450 bags.
The total amount spent on the bags was $600. Some of them cost $1 and the others $2. If the number of $1 bags bought was X and it is given that twice as many $1 bags were bought as $2 bags, the number of $2 bags bought was X/2.
The total cost of the bags in terms of X is 1*X + 2*(X/2). Equate this to 600 and solve for X.
X + X = 600
=> X = 300
The total number of bags was X + X/2 = 300 + 150 = 450
The total number of bags bought was 450
let the no.of bags that cost $1 be x
let the no.of bags that cost $2 be y
acc to Q, X=2Y( you bought twice as many $1 bags as $2 bags) (1)
ALSO 1(X)+2Y=600 (You spent $600 on bags)(2)
USE (1) IN (2)
which implies 4y=600
use this value in (1) we get,x=2(150)=300
so we bought 300+150 =450 in total